Sustainability through Underground Urbanization - Singh, Shubham; Chaudhary, Piyush; Vashisht, Akshay; Singh, Jagdeep (International Journal of Engineering and Technology, 2018)
Urbanization in past few decades has grabbed a huge amount of our agricultural land leading towards various climatic problems as well as endangering our sustainability. Thereby, utilizing the underground earth space instead of using land mass and its resources will transform the lifestyle and will sustain our livelihood. Civilizing and urbanizing underground ecologically enables our sustainability and will contribute to protect the natural resources for future.Â The better utilization of land and sustainable use of earth space will play a vital role to protect our natural resources and maintaining our sustainability. As various research and study shows our planet can sustain up to 11 billion population and we are currently 7.6 billion right now, which is considered to reach deadline till the end of this century. Therefore, utilizing underground earth space will provide enough space for building sector and agriculture sector and will serve the purpose in both ways. Thus, it is quite important to clear the way for sustainable pattern of underground civilization. Â